Occlusal characteristics and prevalence of associated dental anomalies in the primary dentition - Seema Lochib; K.R. Indushekar; Bhavna Gupta Saraf; Neha Sheoran; Divesh Sardana (Springer, 2019)
Introduction: Morphological variations in primary dentition are of great concern to a pediatric dentist as it may pose clinical problems like dental caries, delayed exfoliation and also anomalies in the permanent dentition, such as impaction of successors, supernumerary teeth, permanent double teeth or aplasia of teeth. The present study was conducted to investigate the presence of dental anomalies in the primary dentition of 1000 schoolchildren in the 3-5 year-old age group in Faridabad. Materials and methods: One-thousand schoolchildren were examined using Type III examination (WHO, 1997) for primary molar relationship, occlusal characteristics, primate spaces, physiological spaces and other anomalies of teeth, including number and morphology. Results and conclusions: The prevalence of physiological spaces in maxillary and mandibular arches was 50.9% and 46.7%, respectively, whereas primate spaces were found in 61.7% of the children in the maxillary arch and 27.9% in the mandibular arch. The prevalence of unilateral anterior and posterior cross-bite was 0.1% and 0.8%, respectively, in the present study. The prevalence of hypodontia in the primary dentition was found to be 0.4% and the prevalence of fusion and gemination in the present study was 0.5%. Double teeth (fusion and gemination) and hypodontia were the most common dental anomalies found in the primary dentition in the present study.